Closed loop safety improvement system applied to human factors in aircraft maintenance and inspection. - Renato Augusto da Cunha Pereira (2004)
The present work proposes a method for safety improvement, with emphasis in human factors in the aviation environment. The method consists of step-by-step actions, which demand active participation of the staff of the related area(s), including management. The proposed methodology is based on two models. One model consists of a proactive analysis of the system's "defenses" against human causal factors, which permits as well the detection of latent failures inherent to this system. The other model, widely used in safety assessment, permits the analysis of an occurred event through the modeling of the causal path leading to it. The methodology is then turned to a practical application at EMBRAER, on the tasks of assembly, maintenance and inspection involving pitch trim systems of the EMB 145 aircraft family, and on a case study of a related event. The method and its tools showed themselves useful to promote a critical analysis of the system and the organization from a safety point-of-view, allowing consistent and directed improvements in safety. Closed Loop Safety Improvement System Applied to Human Factors in Aircraft Maintenance and Inspection